2023
DOI: 10.3390/nu15030752
|View full text |Cite
|
Sign up to set email alerts
|

Association between Ultra-Processed Food Consumption and Metabolic Syndrome among Adults in China—Results from the China Health and Nutrition Survey

Abstract: The prevalence of metabolic syndrome (MetS) is increasing and the relationship between ultra-processed food (UPF) consumption and MetS remains uncertain in Chinese adults. This study aimed to examine the longitudinal association of UPF consumption with the risk of MetS and its components in Chinese adults. Adults aged 18 years and above who participated in at least two waves of the China Health and Nutrition Survey (CHNS) in 2009, 2015, and 2018 were included in this analysis. Dietary intake data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The two most recent and extensive prospective cohorts took place in Brazil and China (n = 8,065 and n = 5,147, respectively) and examined the association between UPF intake and the risk for MetS. 54 , 55 Despite considerable differences in the study population as well as in the amount of UPF consumed (median UPF consumption – Brazil 366 g/day; China 16.3 g/day), higher UPF consumption was associated with increased risk for MetS in both cohorts (4 th vs. 1 st quartile; RR 1.19, 95% CI 1.07-1.32 and HR 1.17, 95% CI 1.01-1.35, in Brazil and China, respectively). In contrast, another study in the Brazilian population (n = 896), 56 with a prolonged follow-up time of 14 years, did not find an association.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two most recent and extensive prospective cohorts took place in Brazil and China (n = 8,065 and n = 5,147, respectively) and examined the association between UPF intake and the risk for MetS. 54 , 55 Despite considerable differences in the study population as well as in the amount of UPF consumed (median UPF consumption – Brazil 366 g/day; China 16.3 g/day), higher UPF consumption was associated with increased risk for MetS in both cohorts (4 th vs. 1 st quartile; RR 1.19, 95% CI 1.07-1.32 and HR 1.17, 95% CI 1.01-1.35, in Brazil and China, respectively). In contrast, another study in the Brazilian population (n = 896), 56 with a prolonged follow-up time of 14 years, did not find an association.…”
Section: Resultsmentioning
confidence: 99%
“…(2023, Brazil) 54 Brazilian Longitudinal Study of Adult health (ELSA-Brazil) (7.9 y) n = 8,065 35-74 y (58.7%) Semi-quantitative 114-items FFQ NOVA classification (g/day) Age, gender, BMI, center, race/color, income level, school achievement, smoking status, physical activity, alcohol consumption, energy intake Higher UPF consumption (4 th quartile of >552 g/day vs. 1 st quartile of <234 g/day) was associated with 19% increased risk of incident MetS (RR 1.19, 95% CI 1.07–1.32). A 150 g increase in UPF consumption a day was associated with a 4% higher risk of incident MetS (RR = 1.04, 95% CI 1.02–1.06) Pan F. (2023, China) 55 China Nutrition and Health Survey (CNHS) (6 y) n = 5,147 >18 y (50.0%) 24-hour dietary recall of 3 consecutive days at each survey Cumulative mean UPF intake NOVA classification (g/day) Gender, age, BMI, educational level, place of residence, regions, income level, smoking status, drinking status, metabolic equivalents, urbanicity, energy intake, and dietary factors (protein, total fat, carbohydrate, and sodium intake) Higher UPF consumption (4 th quartile of >36.1 g/day vs. 1 st quartile of <6.5 g/day(was associated with 17% increased risk for MetS (HR 1.17, 95% CI 1.01–1.35; p for trend = 0.047) Magalhães EIDS. (2022, Brazil) 56 The Ribeirão Preto birth cohort (14 y) n = 896 23-25 y (55.7%) Semi-quantitative 83-item FFQ (non-validated) NOVA classification (% of total kCal) NOVA classification (% of total food weight) Gender, age, skin color, educational level, marital status, household income, alcohol consumption, smoking status, physical activity, and energy intake UPF consumption had no association with MetS (% of kCal RR 1.00, 95% CI 0.99-1.01; % of weight RR 1.00, 95% CI 0.99-1.01) Cross-sectional studies Bezerra Barbosa L. (2023, Brazil) 59 Quilombos community-based survey n = 895 19-59 y (100%) 24-hour dietary recall NOVA classification (% of total kCal) NOVA score (ranging from 0 to 23) Model 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Kang and Kim [ 32 ] have shown significant association between fried food consumption and hypertension only in Korean women (in men it was not significant). In turn, the results of a recently published study showed that higher ultra-processed food (UPF) consumption was positively correlated with MetS, and the association was stronger in women, adults aged 45–59 and those living in urban areas [ 33 ]. This may be because UPFs are typically high in added sugars, salt, and saturated and trans fats; their excessive consumption may also result in an increase in the level of C-reactive protein (CRP) and intensification of inflammatory reactions, which increases the risk of MetS [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to research, the global prevalence of MetS has increased over the last 20 years and global prevalence of MetS has been reported to be about 25%, causing huge health, social and economic burdens. 1 , 2 Therefore, early screening and recognition of MetS are of critical importance worldwide, especially in China, a society with high rates of overweight, dyslipidemia and CVD. 3 …”
Section: Introductionmentioning
confidence: 99%